Using the Participation Cube to Conduct Participation Analysis of Development Projects in Zambia and Uganda - and Roberts, Tony; Howard, Jo (The Journal of Development Studies, 2025)
Cooke and Kothari argue that the seductive claims of participation often provide cover for shallow and tokenistic development practices that fail to address unequal power relationships. This paper provides a novel mechanism that documents and enables a three-dimensional analysis of (a) who participates (b) at which project stages and (c) at what level of agency and power. No other mechanism was found in the literature for systematically tracing and analysing changes in power relationship along all three dimensions. The application of this ‘participation tracing’ approach to two case study projects in Zambia and Uganda identified new opportunities to address power inequities thus moving in the direction of what Hickey and Mohan refer to as transformative participation. The method has only been applied retrospectively to date. Further research is necessary applying the method proactively in project planning and during implementation as a form of participatory project assessment.
Keywords: Uganda; Zambia; analysis; cube; evaluation; participation; tracing